Language and Teaching Materials in ELT : An EIL approach - Cavalheiro, Lili (2017)
The current cultural, functional and linguistic multiplicity associated with the English language has led to the pressing need not only to reassess essential notions in English Language Teaching (ELT), but also to reconsider traditional pedagogical practices. Until now, for instance, the decision regarding which instructional variety should be used in a curriculum was generally made without much thought; the choice was mainly centered on already previously established concepts or on the status quo (with particular prominence being given to Standard British or American English). But, when considering the present use of English as an international language, several aspects should be further considered as well, namely: students’ needs and goals, teachers’ capability and accessible resources. The aim of this article is therefore to introduce readers to central issues like language diversity in ELT (not only in terms of native speaker varieties, but also regarding the need to develop communication skills for different communicative situations), and the importance of adapting and creating teaching materials for classroom use. Regarding the latter issue, particular reference is made to creating materials for effective language learning, as well as to how an international perspective can be incorporated into ELT materials so as to prepare students to communicate successfully in a variety of contexts.